2021
DOI: 10.5603/arm.a2021.0035
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Profile and Factors Associated with Severity of the Disease Among Polish Patients Hospitalized Due to COVID-19—An Observational Study

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Data included in this study were collected during the first two waves of the COVID-19 pandemic in Poland. During the first wave of the COVID-19 pandemic (the first half of 2020), numerous research centers and COVID-19-dedicated hospitals had published their own experiences on the clinical characteristics of COVID-19 patients [17][18][19]. Often these publications are based on data on the limited number of COVID-19 cases, so the prevalence of ARDS among COVID-19 patients may be overestimated [12,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data included in this study were collected during the first two waves of the COVID-19 pandemic in Poland. During the first wave of the COVID-19 pandemic (the first half of 2020), numerous research centers and COVID-19-dedicated hospitals had published their own experiences on the clinical characteristics of COVID-19 patients [17][18][19]. Often these publications are based on data on the limited number of COVID-19 cases, so the prevalence of ARDS among COVID-19 patients may be overestimated [12,14].…”
Section: Discussionmentioning
confidence: 99%
“…As of 15 December 2021, a total of 3,881,348 laboratory-confirmed COVID-19 cases and 89,714 COVID-related deaths were reported [10]. Data on the clinical characteristic of COVID-19 patients in Poland are mostly limited to single-center studies [11,17,18]. A study carried out between 16 March and 7 April 2020 in one of the biggest COVID-19-dedicated hospitals showed that of the 169 patients hospitalized with COVID-19, 24.3% had developed ARDS [19].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective analysis of data from Wuhan showed that the MEWS was accurate in predicting in-hospital mortality in elderly patients with SARS-CoV-2 infection [ 46 ]. A small Polish study also showed that the MEWS predicted a severe course of SARS-CoV-2 infection [ 47 ]. The MEWS, which appears to be reliable and easy to assess, was found to be useful in predicting neurological worsening in a cohort of more than 7000 neurocritically ill patients with COVID-19 [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be stressed that, according to the literature on the subject, the presence of comorbidities is a significant risk factor for in-hospital mortality from COVID-19. Many authors emphasize that patients with diabetes, renal failure, heart failure, COPD, and history of stroke or cancer have a higher risk of mortality [ 47 , 52 60 ].…”
Section: Discussionmentioning
confidence: 99%